FAKTOR – FAKTOR PENYEBAB RENDAHNYA PERHATIAN SISWA TERHADAP PERGELARAN SENI BUDAYA (TARI) DI SMP NEGERI 1 BANGKINANG KOTA - Kartika, Winny; Astuti, Fuji (SENDRATASIK UNP, 2019)
Abstract This article aims to describe the factors that cause low attention of students toward the performance of cultural arts (dance) in SMP Negeri 1 Bangkinang Kota. The object of research was students of class IX KH. Ahmad Dahlan.Type of the research was qualitative study with using descriptive method. The research was conducted in the 2018/2019 school year in SMP Negeri 1 Bangkinang Kota. The main instrument in this research was the researcher and it was supoorted by measuring tool in the form of observation format. Techniques of data collection were done through literature study, observation, and documentation. In data analysis, it was done by conducting descriptive qualitative research.The result shows that students' attention are influenced by internal and external factors. The internal factors tend to cause low students’ attention in art performance that are obligation, exercise, listening and thinking. Meanwhile, the external factors that cause low students’ attention are from the teachers, the school facilities and the infrastructure as well as the school economic in the SMP Negeri 1 Bangkinang Kota. Keywords: The Student Attention, Art Performance, Dance